2012
DOI: 10.1021/co300022f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysubstituted 2-Piperidinones via a Michael Addition/Nitro-Mannich/Lactamization Cascade

Abstract: An efficient and practical method has been developed for the diversity-oriented synthesis of polysubstituted 2-piperidinones via four-component reaction between substituted nitrostyrenes, aromatic aldehydes, ammonium acetate, and dialkyl malonates for the generation of a wide range of structurally interesting and pharmacologically significant compounds. It is worth mentioning that in the course of this reaction, the formation of products was highly stereoselective. Two differently stereochemical classes of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Wang et al disclosed an interesting approach toward polysubstituted 2-piperidinones 27 and 28 via four-component reaction between substituted nitrostyrenes 1a, aromatic aldehydes 24, dialkylmalonates 25 and ammonium acetate 26 (Scheme 6). 14 Reactions were carried out by stirring the mixture of a dialkylmalonate 25 (2 mmol), a nitrostyrene 1a (2 mmol), and sodium hydroxide (160 mg, 4 mmol) in 15 mL of methanol or ethanol at 0 C for 45 min, followed by increasing the reaction temperature to rt and addition of an aromatic aldehyde 24 (2 mmol) and ammonium acetate 26 (230 mg, 3 mmol), and reuxing the reaction mixture for 40 h. The electronic properties of substituents on the nitroalkenes and aldehydes do not have signicant effect on the reaction yield. It is interesting that depending on the position of substituents on the structure of aromatic aldehydes, different stereoisomers can be obtained under similar reaction conditions.…”
Section: Piperidinone Derivativesmentioning
confidence: 99%
“…Wang et al disclosed an interesting approach toward polysubstituted 2-piperidinones 27 and 28 via four-component reaction between substituted nitrostyrenes 1a, aromatic aldehydes 24, dialkylmalonates 25 and ammonium acetate 26 (Scheme 6). 14 Reactions were carried out by stirring the mixture of a dialkylmalonate 25 (2 mmol), a nitrostyrene 1a (2 mmol), and sodium hydroxide (160 mg, 4 mmol) in 15 mL of methanol or ethanol at 0 C for 45 min, followed by increasing the reaction temperature to rt and addition of an aromatic aldehyde 24 (2 mmol) and ammonium acetate 26 (230 mg, 3 mmol), and reuxing the reaction mixture for 40 h. The electronic properties of substituents on the nitroalkenes and aldehydes do not have signicant effect on the reaction yield. It is interesting that depending on the position of substituents on the structure of aromatic aldehydes, different stereoisomers can be obtained under similar reaction conditions.…”
Section: Piperidinone Derivativesmentioning
confidence: 99%
“…2d Recently, we developed the diversity-oriented synthesis of alkyl 5-nitro-2-oxo-4,6-diaryl piperidine-3-carboxylates via four-component reaction from substituted nitrostyrenes, aromatic aldehydes, ammonium acetate, and dialkyl malonates. 4 Then we made a try for a selective decarboxylation of alkyl 5-nitro-2-oxo-4,6-diaryl piperidine-3-carboxylates to prepare 4,6-diaryl-5-nitropiperidin-2-ones and found that the reaction did not work. Herein we envisioned the Michael, aza-Henry and lactamization reaction in a single operation to give 4,6-diaryl-5-nitropiperidin-2-ones directly.…”
Section: Figure 1 Ftase Inhibitor 3-nitropiperidine Derivativesmentioning
confidence: 99%
“…Since only two diastereomers were detected in most cases, the minor diastereomer 4 0 could be a tautomer of major diastereomer 4 through the formation of N-oxide oxime 10. 32 Synthesis of 4a was carried out using 0.5 mmol of 6a and 30 mg of cat-1 to evaluate catalyst recovery. Aer completion of the one-pot reactions, the concentrated reaction mixture was loaded onto a uorous SPE cartridge.…”
mentioning
confidence: 99%